STUDI EKSPLORASI PENGALAMAN PEKERJA GENERASI Z TERKAIT PHK MASSAL - Zumhas, Churin Sukmadina (FEB Universitas Sam Ratulangi Manado, 2024)
This study is motivated by the prevalent issue of mass layoffs within the start-up landscape, where the inherently volatile nature of start-ups often leads to precarious working conditions. Start-ups, driven by the pursuit of innovation and rapid growth, frequently resort to mass layoffs as a cost-cutting strategy, leaving employees in a precarious position. This research endeavors to investigate the multifaceted challenges encountered by Generation Z “survivors” in the Indonesian start-up ecosystem following mass layoffs. It seeks to comprehend the emotional, psychological, and social consequences of these layoffs, as well as the broader issue of job precarity affecting this demographic. This study employed a qualitative research methodology, primarily involving in-depth interviews with 13 Generation Z survivors. This study involving in-depth interviews with affected Generation Z employees. This approach facilitates a profound and interpretative understanding of the nuanced perspective on the emotional consequences experienced by Generation Z employees post mass layoffs in the start-up environment in Indonesia.